THE APPLICABILITY OF LAND ALLOCATION APPROACH FOR POST-DISASTER HOUSE CONSTRUCTION IN KUALA KRAI - Mohamed Saraf, Mohamad Haizam; Mohd, Thuraiya; Che Pin, Siti Fairuz; Abdullah, Mohd Nasurudin; Nordin, Tajul Edrus (PLANNING MALAYSIA, 2019)
Despite 2,374 units of houses were destroyed during the 2014 major floods in Kelantan, the governments had only manage to build 143 units of post-disaster houses due to lack of land to accommodate the flood victims because of land ownership constraints. Current practice of post-disaster house reconstruction in Malaysia only accommodate victims with land ownership. The flood victims without land do not have the means or money to buy new land for the construction of the post-disaster house. A land allocation policy for victims without land has yet to be introduced in Malaysia. Using a case study approach, the thrust of this research is to highlight the need of land allocation approach for the flood victims who are without land for post-disaster house construction. Therefore, a semistructured interview was conducted on twelve experts, from the field of land law, policies and administrations, to gauge their perceptions in the applicability of land allocation approach in post-disaster house construction. Data from the interviews were analysed using content analysis technique. Findings from the analysis showed that the experts recommended the state alienation approach in accordance with National Land Code 1965 to allocate land for an emergency, temporary shelters and post-disaster house construction. Land allocation policy can assist government in ensuring that land to shelter disaster victims can be made available after the disaster.